Air quality inside an underground road tunnel system - Ng, Wee Khiang. (2010)
Traffic-induced emissions are one of the main contributors to air pollution around the globe. Even Singapore, a well developed cosmopolitan country, is not spared from the escalating threats of air pollution. In Singapore, the primary contributors to air pollution are from industrial related emission, traffic-induced emission and haze. With the increase in air pollutions, both human health and the environment will be affected. Human cardiovascular and respiratory system will be affected as the consequences of air pollution. Hence, constant monitoring of the current air quality is essential to the wellness of the general public especially the elderly. The project is a detailed study of the air quality along a 600m sector of the 8.5km Kallang-Paya Lebar Expressway (KPE). The monitoring and air sampling were carried out on 5th March 2010 over a 2 day period. Locations for the in situ monitoring were in the South Bore direction along P29K and P23K. The former is located near the saccardo nozzles that inject fresh cool air into the tunnel while the latter is only ventilated via the jet fan system. Street monitoring was also conducted as a control of the internal conditions of the tunnel. The purpose of the project is to monitor and study the ambient air quality of the two locations. Relationships of the various parameters that affect the air quality of KPE will be evaluated. Physical parameters such as temperature and relative humidity will be studied along with the major air pollutants: Particulate Matters (PMs), Benzene Toluene Ethyl-benzene and Xylene (BTEX), Sulfur Oxide (SOx) and Carbon Monoxide (CO). The results of the study show that average interior temperatures recorded are 6.7oC higher than that of the tunnel thermal sensors. It was deduced that the median temperature of P29K is 0.6oC higher than P23K. Concentration of PM2.5 was observed to be greater in P23K than P29K on Friday morning but lower on the Saturday morning. The primary contributors to the PMs are particles with aerodynamic diameters in the range of 5.0-10.0 m. SOx concentrations are monitored to be higher in P23K than in P29K for both days while median CO level at 4.48ppm was consistent throughout the air quality monitoring. In the context of the organic compounds, Toluene and Xylene level are greater on a weekday with Toluene the most prominent hydrocarbons among the BTEX group. Generally, most studied parameters have good correlation with traffic volume. Therefore, an enhanced tunnel air quality management should be developed to improve the travel experience of the KPE commuters. Future planning for the MCE can also benefit through the success of the air quality management system.